Hank Bull: Connexion. BURNABY ART GALLERY - Seller, Shyla (Archivaria, 2017)
Hank Bull: Connexion. BURNABY ART GALLERY, BURNABY, BRITISH COLUMBIA 20 January–6 April 2017. Curated by JONI LOW and PAN WENDT